Universalismo, guerra e profecia: Maranhão no tempo da Restauração Portuguesa nos escritos de Padre Antônio Vieira (1641-1653) - PEREIRA, Nathalia Moreira Lima (2016)
The present study analyzes the role of Maranhão in the political-prophetic writings of Father Antônio Vieira. In the context of the Restoration War (1640-1668), the vast work of Father Antonio Vieira, which includes letters, sermons and his prophetic-political writings, reinvents the theme of universalism to include the newly restored nation in the plans for recognition and legitimacy of Their independence. However, his writings are beyond the European space, setting also in Portuguese America and in the State of Maranhão itself. The present 9study investigates the impacts of the Restoration and the Luso-Castilian war in this territory and in what we can call the Equatorial Atlantic. Thus, we seek to understand how associated elements such as Vieira's diplomacy, the war of restoration, the Equatorial Atlantic and the State of Maranhão are integrated into a project at the same time of political conquest and conversion, reinvented within the limits of portuguese providentialism.